Clinicopathological characteristics and survival outcomes of women aged ≤45 and >45 years with endometrial adenocarcinoma in tertiary referral hospital: a 21-year cohort study - Tarinee Manchana; Pinyada Panyavaranant; Juthamas Rattanachaipipat (BMJ Open)
Objective This study aimed to compare clinicopathological characteristics and oncological outcomes in patients with endometrial cancer aged ≤45 and >45 years, with a focus on identifying distinct traits and prognostic factors in younger patients.Design A retrospective cohort study.Setting The study was conducted at King Chulalongkorn Memorial Hospital, Bangkok, Thailand, with a restricted study population from 1996 to 2016.Participants A total of 1114 patients diagnosed with endometrial cancer and underwent surgery were strictly selected, excluding those who had received primary radiotherapy or had uterine sarcoma. Among the population, 188 patients (16.9%) were ≤45 years old and 926 patients (83.1%) were >45 years old.Outcome measures The primary outcome measures were disease-free survival (DFS) and overall survival (OS) at 5, 10 and 15 years, with an analysis of survival rates based on patient age groups and prognostic factors.Results Younger patients (≤45 years) displayed significantly higher rates of obesity, nulliparity and polycystic ovary syndrome (PCOS), as well as favourable pathological characteristics such as well-differentiated tumours and lower rates of myometrial invasion. They also exhibited better long-term survival outcomes, the DFS rates at 5, 10 and 15 years were 89.6% (95% CI: 84.0 to 98.3), 85.9% (95% CI: 79.0 to 90.6) and 76.8% (95% CI: 63.3 to 85.9), respectively, compared with 77.6% (95% CI: 74.6 to 80.2), 69.2% (95% CI: 65.6 to 72.5) and 53.5% (95% CI: 48.0 to 58.6) in the older group. Similarly, the OS rates at 5, 10 and 15 years were 94.7% (95% CI: 90.1 to 97.2), 91.7% (95% CI: 85.4 to 95.3) and 74.0% (95% CI: 51.7 to 87.2), respectively, compared with 86.9% (95% CI: 84.4 to 89.0), 76.6% (95% CI: 73.0 to 79.7) and 60.7% (95% CI: 55.0 to 65.8) in the older group. Independent prognostic factors consist of non-endometrioid histology, involvement of the lower uterine segment and cervix, omental metastasis, lymphovascular invasion and advanced stage.Conclusions Young patients with endometrial cancer exhibit distinct favourable clinicopathological characteristics associated with better oncological outcomes compared with older patients. However, certain aggressive disease features should be taken into consideration as they have a negative influence on prognosis significantly. These insights emphasise the need for targeted management strategies and further research.